Hubungan Umara dan Ulama dalam Membentuk Kehidupan Sosio-Relijius di Aceh Darussalam Masa Sultan Iskandar Muda (The Relation of Umara and Ulama in Shaping Socio-Religious life in Aceh Darussalam under Sultan Iskandar Muda's Period) - Gazali Gazali (Jurnal Penelitian Hukum De Jure, 2016)
ABSTRACTUmara (the ruler) and ulama (islamic scolar) are two elite groups which are showing an elemental instrument for developing Aceh Darussalam. In the age of Iskandar Muda, there is a truly work-grouping which are filling with many work of them. In the capital kingdom, Hamzah Fansuri and Syamsuddin as-Sumatra'i had played a multidimensional role for strengthern and eriching Aceh as a central Islamic knowledge and Malay literature in South East Asia. They had known as Islamic scholar, diplomat and bishop. Their existence in the sultan palace helped other Sultan's cabinet for finishing many social problem, include acts arragement, legalizing an prudence and many more. In the other hand, the relation of ulama-umara also seen in village or out-palace life. There are a social system which is based on their activities. In people of Aceh's ayes, their position regarded as a leader of social and spiritual life. Meunasah, a place that is used for, daily islamic rituals studying many various of islamic knowledge, discussion about social needing, is crowded by their activities. Teungku meunasah, ulama that is leading in meunasah, is the most outstanding men in their society. With keuchik, imeum mukim or uleebalang, they applicate the idea of developing humanity. There is a passion which is created from their bounderies. This article talks about how the relation of umara and ulama is working. This explanation presented their mutual undersatnsing to solve various problem of social-religious life. From that point, we can get some pictures which is describes how the condition of dynamic of social structure of Aceh.Keywords: Relation, Mutual-Working And Social-Religious LifeABSTRAKUmara (pemimpin) dan ulama (sarjana Islam) adalah dua grup elit yang menampilkan instrumen dasar dari perkembangan Aceh Darussalam. Di masa Sultan Iskandar Muda, banyak ditemukan produk-produk kerja sosial dari kerjasama mereka. Di ibukota kerajaan, Hamzah Fansuri dan Symasuddin as-Sumatra'i memainkan peran multiaspek guna mengembangkan Aceh sebagai pusat keilmuan dan sastra Melayu di Asia tenggara. Mereka dikenal sebagai sarjana Islam, diplomat, dan Syeikhul Islam. keberadaan mereka di istana Aceh ikut membantu Sultan dalam memecahkan pelbagai masalah sosial, termasuk menyusun undang-undang, menerbitkan kebijakan dan lain sebagainya. Di sisi lain, hubungan umara dan ulama juga terlihat di pedesaan Aceh. Di sana terdapat sistem sosial yang terbentuk karena keduanya. Di mata orang Aceh, kedudukan mereka diakui sebagai pemimpin dalam kehidupan sosial dan spiritual. Meunasah, suatu tempat yang biasa digunakan sebagai beribadah sehari-hari, belajar ilmu-ilmu agama dan bermusyawarah, diramaikan oleh aktivitas mereka. Teuku meunasah, ulama yang betanggung jawab di meunasah, adalah orang yang dimulyakan di lingkungannya. Bersama dengan keuchik, imeum mukim dan uleebalang mereka mengaplikasikan gagasan untuk mengembangkan kemanusiaan. Hubungan mereka dilingkupi oleh suatu kepaduan dalam bertindak. Artikel ini menerangkan tentang bagaimana relasi umara-ulama berjalan. Pemaparan ini menghadirkan suatu kesepemahaman bersama untuk menyelesaikan masalah sosio-relijius masyarakat. Pada titik ini, kita bisa memperoleh gambaran yang menjelaskan bagaimana kondisi pasang surut struktur sosial di Aceh.Kata kunci: Relasi, Kerja Sama, Kehidupan Sosio-Relijius.